Association between depression and cardiometabolic multimorbidity: A protocol for a systematic review and meta-analysis - Myo Zin Oo; Soe Sandi Tint; Somdeth Bodhisane (PLoS ONE, 2026)
Introduction Cardio metabolic multimorbidity (CMM) is increasingly prevalent and associated with substantial morbidity and mortality, yet the role of depression in the clustering of cardiometabolic conditions has not been comprehensively synthesized. This systematic review and meta-analysis aims to synthesize observational evidence on the association between depression and cardiometabolic multimorbidity and to estimate the prevalence of cardiometabolic multimorbidity among adults with depression. Methods The protocol was registered in PROSPERO (CRD420251079959) and is reported in accordance with PRISMA-P guidelines. We will include observational studies (cohort, case-control, and cross-sectional) involving adults aged ≥18 years that examine the association between depression and CMM. Depression must be assessed using validated diagnostic criteria, standardized screening instruments, or clinical codes. CMM will be defined as the coexistence of two or more cardiometabolic diseases, including at least one metabolic and one cardiovascular condition. Relevant studies will be identified through systematic searches of PubMed, Embase, and Scopus from inception to September 2026, without language restrictions. Two reviewers will independently screen studies, extract data, and assess risk of bias using the Newcastle-Ottawa Scale (NOS) for cohort and case-control studies and the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for cross-sectional studies. Random-effects meta-analyses will be conducted to pool adjusted association estimates. Where sufficient longitudinal data are available, longitudinal risk estimates will also be synthesized separately. Pooled prevalence of CMM among individuals with depression will also be estimated. Heterogeneity, publication bias, and subgroup analyses according to age, sex, geographic region, depression ascertainment method, and cardiometabolic multimorbidity definition will be conducted where sufficient data are available. Certainty of evidence will be evaluated using the GRADE approach. Conclusion This systematic review and meta-analysis is expected to improve the understanding of the relationship between depression and cardiometabolic multimorbidity and to inform future research, clinical practice, and public health strategies.